A study of rice blast disease in Kampung Alor Bakat, Kelantan / Muhammad Ilham Ismail - Ismail, Muhammad Ilham (Faculty of Plantation and Agrotechnology, 2016)
Rice is a staple food for most people in the world. This include Malaysia which Malaysian eat rice every day. Moreover rice also is the sources income for farmers. However, the production of paddy is in sufficient because due several problems. Rice blast disease is one of the problems which cause losses of 11-30% annually. In Kampung Alor Bakat, the level of the incidence and severity of rice blast disease is not been updated. This study was carryout to determine the current incidence and severity of rice blast in Kampung Alor Bakat. In Kampung Alor Bakat, the percentage of the incidence and severity of rice blast disease are lower than 50% with the incidence of field 1 is 41.03%, field 2 is 43.93% and field 3 is 30.83%. While the severity offield 1 is 12.44%, field 2 is 14.22 and field 3 is 6.67%. There are several factors that contribute the infection of rice blast disease and in this study the most factors cause the infection of rice blast disease are quantity of fertilizer use, quantity of fungicide use and the water level in the paddy field.